2015
DOI: 10.1007/s00702-014-1362-4
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of monoamine oxidase (MAO) expression in neuropsychiatric disorders: genetic and environmental factors involved in type A MAO expression

Abstract: Monoamine oxidase types A and B (MAO-A, MAO-B) regulate the levels of monoamine neurotransmitters in the brain, and their dysfunction may be involved in the pathogenesis and influence the clinical phenotypes of neuropsychiatric disorders. Reversible MAO-A inhibitors, such as moclobemide and befloxatone, are currently employed in the treatment of emotional disorders by inhibiting the enzymatic degradation of dopamine, serotonin and norepinephrine in the central nervous system (CNS). It has been suggested that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(39 citation statements)
references
References 177 publications
(177 reference statements)
0
39
0
Order By: Relevance
“…Previously, it was reported that MAO‐B activity is significantly increased in specific brain regions in ageing (Fowler et al ., ; Strolin Benedetti and Dostert, ; Cohen, ) and AD (Hirvonen et al ., ) and may contribute to neurodegenerative processes, secondary to ROS production. Furthermore, MAO‐A activity and gene expression have been found to be up‐regulated in different brain areas of AD patients (Burke et al ., ; Emilsson et al ., ; Naoi et al ., ). It was suggested that decreased levels of the CNS monoamines, such as dopamine, noradrenaline and 5‐HT (Adolfsson et al ., ) and an altered monoaminergic neurotransmitter system (e.g.…”
Section: Pathophysiological Targets In Ageing and Admentioning
confidence: 99%
“…Previously, it was reported that MAO‐B activity is significantly increased in specific brain regions in ageing (Fowler et al ., ; Strolin Benedetti and Dostert, ; Cohen, ) and AD (Hirvonen et al ., ) and may contribute to neurodegenerative processes, secondary to ROS production. Furthermore, MAO‐A activity and gene expression have been found to be up‐regulated in different brain areas of AD patients (Burke et al ., ; Emilsson et al ., ; Naoi et al ., ). It was suggested that decreased levels of the CNS monoamines, such as dopamine, noradrenaline and 5‐HT (Adolfsson et al ., ) and an altered monoaminergic neurotransmitter system (e.g.…”
Section: Pathophysiological Targets In Ageing and Admentioning
confidence: 99%
“…Oxidative deamination of MAO substrates that produces hydrogen peroxide and the corresponding aldehyde is selectively prevented by propargylamines (clorgyline and deprenyl) [5]. Many studies have extensively highlighted the role of MAO activity in the central nervous system [68]; however, its relevance in other organs, including the heart, has been investigated only recently. Increasing evidence suggests that, in rodent cardiomyocytes, MAO activity may contribute to NE- and 5-HT-induced hypertrophy, to apoptosis, and to the stimulation of cell glucose uptake by hydrogen peroxide generation [913].…”
Section: Introductionmentioning
confidence: 99%
“…Following the discovery of the lack of MAOA in Norrie disease [217], abnormal regulation of the enzymes implicated in 5-HT metabolism has been known for long to be associated with neuropsychiatric diseases (recently reviewed by Naoi et al [218]). However, it is not known whether the alteration in prenatal or post-natal human life induces such illness.…”
Section: Serotonin Imbalance and 5-ht 3 Receptor Modulation In Human mentioning
confidence: 99%